New class of protein kinase C modulators: from ethnopharmacological to nanoparticles - Isca, Vera M. S. (2023)
Cancer is one of the most common causes of death worldwide. Protein kinase C (PKC) are a class of enzymes often linked to carcinogenesis. Additionally, the development of multidrug resistance (MDR), mainly associated with P-glycoprotein (P gp) is the major cause of failure in traditional cancer chemotherapy. Plectranthus spp. have been used in traditional medicine for various ailments, including cancer, and its bioactive components have been investigated for their potential anticancer effects. In particular, the compound 7α-acetoxy-6β hydroxyroyleanone (Roy, 1) displayed promising antiproliferative activity against several cancer cell lines. This study embarks on an exploration of Roy 1, as a lead compound for the development of novel drugs. The acetonic ultrasound-assisted extraction optimization of Roy 1 (55.2 μg.mg-1 ) from P. grandidentatus was reported. Moreover, the reactivity of Roy 1 was explored to prepare new bioactive esters. Consequently, a new ester derivative and four known compounds were prepared, pointing to the most reactive hydroxyl group at position C12. Moreover, Roy 1 and its selected derivatives 20 and 21, aqueous stability was evidenced. Furthermore, a prediction molecular docking study was done to select the potential royleanone derivatives to modulate PKC. The synthesis of 30 derivatives was building upon molecular docking predictions, and the reactivity findings from Chapter II, including 23 new ester derivatives. Likewise, the synthesis of Roy 1 gold NPs was done, as a preliminary study to improve the low water solubility of these compounds. All derivatives were tested in cancer cells, pointing to the selection of four derivatives (52, 53, 64, and 66) to test in a PKC yeast-based assay, and finally one hit derivative (53) was assessed in PKC enzymatic assay. Notably, promising cytotoxic effects were observed in several derivatives, including 20 (as a PKC-δ activator), 21, and 22 (functioning as P-gp inhibitors), as well as 52, 53, 64, and 66 (in breast cancer cell lines). The analog 53 exhibited remarkable PKC-α activation. The findings described contribute to the expansion of more potent and selective antitumoral agents.